Influences of soil amendments on alfalfa production and soil properties. Issue 1 (24th July 2020) - DeSutter, T. M.; Breker, M.; Chatterjee, A.; O'Brien, P. L.; Wick, A.
Abstract: Millions of acres of agricultural soils in the Northern Great Plains have excessive levels of sodium (Na) which reduces their productivity potentials. Soil function in Na‐affected soils may be improved by soil amendments, but the effectiveness of these amendments is dependent on many site‐specific characteristics. This study investigated how three amendments (with three application rates), gypsum, spent lime (5, 15, and 30 ton ac −1 ), and potassium‐magnesium sulfate (1, 2.5, 5 ton ac −1 ), affected alfalfa ( Medicago sativa L.) production and soil parameters at a site with subsurface tile drainage and a site without tile drainage over 4 yr. Notably, over the course of the study, none of the amendments affected alfalfa production or quality at either site, although the highest rate of potassium‐magnesium sulfate reduced biomass production by about 10%. After 4 yr within the 0‐ to 6‐ in depth, the amendments lowered electrical conductivity (EC) and %Na at the tiled site compared to the control but not at the nontiled site. Moreover, the higher rates of each amendment decreased %Na compared to initial conditions, but after 4 yr, these treatments were not different from the control (alfalfa only). This study determined that the use of a perennial crop, such as alfalfa, may be as effective as amendments in reducing the negative effects of Na on soil properties.